'It can be difficult to find the right words': Parents' needs when breaking news and communicating to children with cancer and their siblings. Issue 4 (13th July 2021) - Kenny, Méabh; Duffy, Katie; Hilliard, Carol; O'Rourke, Mary; Fortune, Gillian; Smith, Owen; Hynes, Geralyn; Higgins, Agnes
Abstract: Purpose: This paper explores parents' experiences of breaking news and communicating to the child with cancer and their siblings, and identifies the supports parents request to help them in this role. This paper represents one component of a wider action research study which employed mixed methods to explore supports needed by parents of children with a cancer diagnosis in the Republic of Ireland. Research Design: This paper reports on the survey phase of the study, which involved the distribution of a postal survey to 550 families of children in cancer treatment and remission. This survey included four open-ended questions exploring parents' experiences of breaking news and communicating about the illness to the ill child and his/her siblings. Descriptive statistics on the profile of the parents were generated with computer software package SPSS and qualitative responses were analyzed using the survey questions as the initial framework. Findings: Parents identified four interventions that helped ease the distress of these difficult conversations: coaching, resources, team engagement, and play therapy. Parents expressed concern for siblings, describing them as "suffering" and "forgotten". Parents requested four sibling-specific interventions: the creation of resources for siblings, therapeutic support, coaching for parent-sibling conversations, standardize a family meeting with the multi-disciplinary team that includes siblings. Implications for Psychosocial Providers: This paper demonstrates how the practical supports requested by parents which are consistent with the principles embedded within the internationally defined psychosocial standards of care could be translated into practice when supporting parents to communicate with children in the context of pediatric cancer.